An Investigation Into the Effects of In Vitro Dilution With Different Colloid Resuscitation Fluids on Clot Microstructure Formation. (November 2016) - Lawrence, Matthew James; Marsden, Nick; Kaczynski, Jakub; Davies, Gareth; Davies, Nia; Hawkins, Karl; Perumal, Sounder; Brown, Martin Rowan; Morris, Keith; Davidson, Simon J.; Williams, Phylip Rhodri; Evans, Phillip Adrian
Abstract : BACKGROUND: Balancing the beneficial effects of resuscitation fluids against their detrimental effect on hemostasis is an important clinical issue. We aim to compare the in vitro effects of 3 different colloid resuscitation fluids (4.5% albumin, hydroxyethyl starch [Voluven 6%], and gelatin [Geloplasma]) on clot microstructure formation using a novel viscoelastic technique, the gel point. This novel hemorheologic technique measures the biophysical properties of the clot and provides an assessment of clot microstructure from its viscoelastic properties. Importantly, in contrast to many assays in routine clinical use, the measurement is performed using unadulterated whole blood in a near-patient setting and provides rapid assessment of coagulation. We hypothesized that different colloids will have a lesser or greater detrimental effect on clot microstructure formation when compared against each other. METHODS: Healthy volunteers were recruited into the study (n = 104), and a 20-mL sample of whole blood was obtained. Each volunteer was assigned to 1 of the 3 fluids, and the sample was diluted to 1 of 5 different dilutions (baseline, 10%, 20%, 40%, and 60%). The blood was tested using the gel point technique, which measures clot mechanical strength and quantifies clot microstructure ( d f ) at the incipient stages of fibrin formation. RESULTS: d f and clot mechanical strength decrease with progressive dilution for all 3 fluids. A significant reduction in d f from baseline was recorded at dilutions of 20% for albumin ( P < .0001), 40% for starch ( P < .0001), and 60% for gelatin ( P < .0001). We also observed significant differences, in terms of d f, when comparing the different types of colloid ( P < .0001). We found that albumin dilution produced the largest changes in clot microstructure, providing the lowest values of d f (= 1.41 ± 0.061 at 60% dilution) compared with starch (1.52 ± 0.081) and gelatin (1.58 ± 0.063). CONCLUSIONS: We show that dilution with all 3 fluids has a significant effect on coagulation at even relatively low dilution volumes (20% and 40%). Furthermore, we quantify, using a novel viscoelastic technique, how the physiochemical properties of the 3 colloids exert individual changes on clot microstructure. Abstract : Published ahead of print September 16, 2016.